ISOLASI DAN IDENTIFIKASI BAKTERI PADA SAMPAH ORGANIK PASAR KOTA PEKANBARU DAN POTENSINYA SEBAGAI RANCANGAN LEMBAR KERJA SISWA (LKS) BIOLOGI SMA - Hardianti, Nia; Sayuti, Irda; ', Yustina (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2016)
Abstract: This research aimed to isolation and identification of bacteria market organic waste Pekanbaru city om march-June 2016. Result of the research use for make a material learning design the form student worksheet in biologi SMA. The research conducted with 2 phase namely experimental research and design or material learning the from student worksheet. Method of the research is purvosive sampling method wich set sampel taked location based on waste spread. Identification of bacteria wich macroscopis observation is cell shape, edge cell and colour cell wall bacteria, gram colour, and Biohchemical test. Result of research showed 10 genus bacteria found from 4 market Pekanbaru city, 10 genus of bacteri consist of genus Enterobacter, Streptococcus, Streptomyces, Holobacterium, Proteus, Eschericia, Neisseria, Pseudomonas, Klebseilla and Bacillus. Result og the reseasch isolation and identification of bacteria market organic waste Pekanbaru city can use as material learning design the from student worksheet on eubacteria matter biology SMA.Keywords: Isolation, Identification, Bacteria, Waste, Design, Student Worksheet.